Soft power of Korean popular culture on consumer behaviour in Malaysia - Gan, Xi Ni (2019)
In line with varieties of globalized products and images that could get in Malaysia, especially when information could be spread easily and fast in this modern world, people’s consumer behavior can be subjected to a range of influences. One of the influences is the Korean popular culture that dominated through entertainment like Korean Wave (Hallyu), K-dramas, movies, and K-pop. Despite the extensive research on people showing interested attitude towards Korean Wave and how they attracted towards Korean Wave, there is lack of research on their consumer behaviour towards Korean products. Hence, there is a need to look into this aspect because consumer behaviour is believed to have its own unique thinking and decision making. Therefore, this study explored the relationship between Korean popular culture and consumer behaviour towards Korean products and look into their perceptions towards Korean products. This study uses in-depth interview to seek for the detailed opinion of participants and surprisingly the reason that most of they choose to consume Korean products is because of good quality rather than idolism.